2012
DOI: 10.1124/jpet.112.193193
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Coffee Drinking, and Ingestion of Charcoal-Broiled Beef as Potential Modifiers of Drug Therapy and Confounders of Clinical Trials

Abstract: A pathway of research is described, leading from the finding of an inhibitory effect of 3-methylcholanthrene on the carcinogenicity of an aminoazo dye, to the induction of drug-metabolizing enzymes by 3-methylcholanthrene, benzo[a]pyrene, and other polycyclic aromatic hydrocarbons, to the demonstration of enhanced drug metabolism in cigarette smokers, coffee drinkers, and people who eat charcoal-broiled beef. The results of these studies indicate that cigarette smoking, coffee drinking, and the ingestion of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…This is relevant because cigarette smoking is known to induce P450 1A. 31 P450 2D6 was capable of generating M5 in vitro, as demonstrated from incubations with recombinant enzyme and human liver microsomal fractions; however, P450 2D6 is likely not a significant contributor to sunitinib reactive metabolite generation based on its low catalytic efficiency observed in kinetic assays. M3 and M5 were also formed by the extrahepatic P450s 1A1 and 2J2.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because cigarette smoking is known to induce P450 1A. 31 P450 2D6 was capable of generating M5 in vitro, as demonstrated from incubations with recombinant enzyme and human liver microsomal fractions; however, P450 2D6 is likely not a significant contributor to sunitinib reactive metabolite generation based on its low catalytic efficiency observed in kinetic assays. M3 and M5 were also formed by the extrahepatic P450s 1A1 and 2J2.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is one of the main factors contributing to the variability of riociguat exposure; quantitative variations in smoking habits or other environmental or dietary factors that induce CYP1A1 (e.g. consumption of cruciferous vegetables or charcoal-broiled meat [ 55 , 56 ]) may contribute to interindividual variability in the separate subpopulations of smokers and non-smokers [ 15 ]. However, there is no reason to suspect that these factors differed substantially between smokers and non-smokers in the riociguat studies, and the effect of smoking on riociguat exposure has been observed in studies controlled for diet and environment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and drug use, including opioids, cocaine, and methamphetamines, have a major dose–response influence on medication adherence and interactions with commonly prescribed medications [68, 112115]. Alcohol and tobacco can influence drug clearance and activity levels directly and through effects on liver and kidney function, with important clinical impacts [116119]. Use of controlled medications other than how they were prescribed or solely for the effect they provide (non-medical use) can result in over-sedation, overdose and death [120–122].…”
Section: Factors Contributing To Polypharmacy’s Harmsmentioning
confidence: 99%